PLZF and its fusion proteins are pomalidomide-dependent CRBN neosubstrates - Nobuyuki Shimizu (Nature Portfolio, 2021)
Shimizu et al. identify PLZF/ZBTB16 and its fusion proteins as pomalidomide-dependent neosubstrates of the cereblon E3 ligase. The authors also report that pomalidomide induces their degradation and thereby exerts its anti-cancer effect in leukemic cells expressing the fusion proteins.